1983
DOI: 10.1007/bf00423246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood ammonia, lactate and amino acids in relation to workload during bicycle ergometer exercise in man

Abstract: Whole body exercise at intensities up top 50% VO2max has no effect on the concentration of blood ammonia but a threefold rise in blood ammonia is observed at workloads up to maximal. There is a linear relationship between blood ammonia and lactate production during exercise which suggests that the two processes may be linked to a common process of short-term energy provision. Blood glutamine and blood alanine both show rises linearly related to power output during exercise, suggesting that if these amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
4

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 13 publications
5
48
1
4
Order By: Relevance
“…Tables 2 and 3 show mean¡SD plasma ammonia and blood lactate responses to incremental cycle exercise. Resting plasma ammonia concentrations were similar for COPD and similaraged subjects and within published ranges [7,9,24]. Plasma ammonia concentration increased during exercise in subjects with COPD (p,0.001) and similar-aged subjects (p,0.001) and continued to increase at 2 min after exercise, before declining towards baseline at 5 min after exercise.…”
Section: Incremental Exercisesupporting
confidence: 72%
“…Tables 2 and 3 show mean¡SD plasma ammonia and blood lactate responses to incremental cycle exercise. Resting plasma ammonia concentrations were similar for COPD and similaraged subjects and within published ranges [7,9,24]. Plasma ammonia concentration increased during exercise in subjects with COPD (p,0.001) and similar-aged subjects (p,0.001) and continued to increase at 2 min after exercise, before declining towards baseline at 5 min after exercise.…”
Section: Incremental Exercisesupporting
confidence: 72%
“…Ammonia is a product of adenine nucleotide deamination, which occurs during intense exercise when muscle ATP resynthesis rates cannot meet demand. Blood ammonia accumulation has been shown to occur during intense exercise in healthy humans (19,20), and we have recently confirmed that this also occurs during maximal incremental exercise in patients with COPD (17).…”
Section: Discussionsupporting
confidence: 68%
“…In fact it is well documented that, at least with endurance exercise, absolute oxidation of the amino acid leucine increases (4,31,45,67,69,78,92). This effect appears to be greatest at high exercise intensities (4,69,78,92) and in trained individuals (23, 49). Further, the magnitude of this response is substantial and under prolonged endurance exercise conditions can approach daily requirements (31).…”
Section: Possibilitymentioning
confidence: 99%